The Degree of Practicing Administrative Corruption by junior High Schools’ Principals within the Green Line and its Relationship to Jop Satisfaction among Teachers and Instructors from their Point of View - Hmodi, Rafat Salama; Olimat, Saleh Nasser (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the administrative corruption degree in junior high schools within the Green Line in Triangle region cities, and its relationship to job satisfaction among teachers and instructors from their point of view. This research is a descriptive correlational survey type that was implemented using a two- axis and eight- domain questionnaire as a tool. The sample consisted of (390) participants of teachers and instructors. The sample was selected randomly during the academic year 2020\2021.The results of the study showed that administrative corruption, from the sample's point of view, obtained an overall average (3.25 out of 5) with a practice rating of (medium). As for the sub- domains; The corruption related to employees got the highest average of (3.75) with a rating of (large), then material with an average of (3.31) then transactions with an average of (3.17) and finally corruption in facilities with an average of (3.05), all of them with a rating of practice, (medium). As for the job satisfaction axis of teachers and instructors, it was obtained an overall average (3.27 out of 5) with a degree of satisfaction (medium). The level of the domains; Satisfaction with the school environment got the highest average (3.66), with an average (significant) degree, then satisfaction with qualification and training with an average (3.21), then satisfaction with leadership with an average (3.04), and finally financial satisfaction with an average (2.94), all with a degree of satisfaction (medium). The results also showed a relationship between job satisfaction and administrative corruption with a negative relationship that amounted to (r =- 0.29; p < 0.1), and corruption is statistically significant. The study also showed that there are statistically significant differences between the average estimates of the study sample of the level of their estimates of administrative corruption and their job satisfaction in the four areas, according to the gender variable in favor of females, and according to the qualification variable in favor of the bachelor's holders, and according to the experience variable in favor of those with less experience, and according to the school variable in favor of teachers and instructors from private schools.Based on the results of the study, the researcher presented a set of recommendations to reduce administrative corruption and increase the satisfaction of teachers and instructors, including: Working to provide an organized educational environment in educational institutions that reflects the state of interdependence between the goals put forward by the administration and teachers and effective participation between the different parties to achieve the desired goals and bring out a future generation. It was also suggested to conduct complementary research on the subject.
Keywords: administrative corruption; job satisfaction; teachers and instructors; Green Line; relationship